Tuberculosis in the African continent: A comprehensive review. Issue 1 (March 2015) - Chatterjee, Delphi; Pramanik, Arun K.
Abstract: Tuberculosis continues to be a major global health problem, causing an estimated 8.8 million new cases and 1.45 million deaths annually. New drugs in the 1940s made it possible to beat the disease, and consequently, the number of cases reduced drastically. Fast-forward a few decades, drugresistant strains of varied virulence are reported consistently, disease is again on the rise and the treatment has not kept pace. Tuberculosis is the leading cause of death among HIV-infected persons in many resource-constrained settings however, it is curable and preventable. The unprecedented growth of the tuberculosis epidemic in Africa is attributable to several factors, the most important being the HIV epidemic. Analysis of molecular-based data have shown diverse genetic backgrounds among both drug-sensitive and MDR TB isolates in Africa presumably due to underlying genetic and environmental differences. The good news is that there have been important advances recently in TB drugs and diagnostics. Despite the availability of revolutionary tests that allow for faster diagnosis and of new drugs and regimens that offer better and safer treatment it is now becoming clearer that national efforts on TB control should be enhanced and focus on improving the quality of prevention, diagnosis, treatment and care services; strengthening program management, implementation and supervision. This review is an assessment of the trend in TB in Africa.